Sentir com imagens: a vida de 50 retratos fotográficos - Roque, Inês (2014)
Submitted by Susana Santos (susana.santos@iade.pt) on 2014-12-17T13:01:23Z No. of bitstreams: 1 tesefinal_inesroque.pdf: 151669576 bytes, checksum: 7ea8a4123d31c8878ab1581820f5fecf (MD5)